2013
DOI: 10.15376/biores.9.1.293-302
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Colorimetric Changes in Eucalyptus grandis Wood after Heat Treatment

Abstract: Planted forests can meet the world's demand for wood. In Brazil, eucalypt species are cultivated on a large scale, but their dimensional instability and color limit their use, which makes heat treatment necessary. The aim of this study was to evaluate physical and colorimetric properties of Eucalyptus grandis after heat treatment at 140, 170, 200, and 230 °C for 3 h. Mass loss, shrinkage, equilibrium moisture content, volumetric swelling, fiber saturation point (FSP), and colorimetric parameters were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 32 publications
1
23
0
10
Order By: Relevance
“…As thermal modification intensity increased, at 160 and 180 °C, the eucalypt samples tended to present a less reddish colour. This trend has also been observed in studies with Eucalyptus grandis by Zanuncio et al (2014), Cademartori et al (2013) and Moura and Brito (2011) for different thermal treatment process. The reduction of red colour tone in the thermally modified wood is associated with the volatilization of phenolic extractives that confer a red colour to the eucalypt wood (Pincelli et al 2012).…”
Section: Quantification Of Colour Of Untreated and Thermally Modifiedsupporting
confidence: 79%
See 2 more Smart Citations
“…As thermal modification intensity increased, at 160 and 180 °C, the eucalypt samples tended to present a less reddish colour. This trend has also been observed in studies with Eucalyptus grandis by Zanuncio et al (2014), Cademartori et al (2013) and Moura and Brito (2011) for different thermal treatment process. The reduction of red colour tone in the thermally modified wood is associated with the volatilization of phenolic extractives that confer a red colour to the eucalypt wood (Pincelli et al 2012).…”
Section: Quantification Of Colour Of Untreated and Thermally Modifiedsupporting
confidence: 79%
“…Usually, fast-growing trees from forest plantations present wood of inferior quality in such attributes as colour, density and mechanical properties, which makes that it fetches a lower price in the timber market (Thulasidas et al 2006, Moya andBerrocal 2010). The surface colour and dimensional instability limit the use of the Eucalyptus grandis wood (Zanuncio et al 2014). During the thermal modification process, the wood becomes more dimensionally stable and the wood colour is changed and acquires a dark tonality, what could be advantageous for species with unappealing colour like eucalypt .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a given temperature, the quantity of each degradation product increases progressively as the treatment duration increases (Candelier et al 2013c). Zanuncio et al (2014), using eucalyptus treated between 140 and 230°C during 3 hours, found that mass loss varied from 0.33 % (140°C) to 0.63 % (170°C), to 2.73 % (200°C) and to 10.73 % (230°C). Olarescu et al (2014) studied the mass loss of lime wood (Tilia cordata Mill.)…”
Section: Introductionmentioning
confidence: 99%
“…The highest value for the anisotropy in clone D indicates that its wood has restricted use in places with high humidity variation. However, treatments such as acetylation (Xie et al, 2013;Himmel et al, 2015) and heat treatment (Korkut, 2012;Zanuncio et al, 2014b) can reduce the variation in the wood dimensions and allow its use in such places.…”
Section: Characterization Of the Wood Physical Propertiesmentioning
confidence: 99%